The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3167/latiss.2020.130102
|View full text |Cite
|
Sign up to set email alerts
|

Higher education in the paradigm of speed

Abstract: Studies often highlight how standardisation and consent are manufactured through the European Bologna Process (Brøgger 2019; Gibbs et al. 2014; Lawn and Grek 2012). This article shows how students’ conduct is still governed by multiple logics and dilemmas. The context for the article is the Bologna Process and the way it has been applied by the Danish government in the 2014 reforms that sought to fast-track the completion of student degrees. It analyses the impact of changes on students’ conduct through a seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Students are able to resist, change and play with expectations towards them (Brooks, 2022; Tomlinson, 2017). This shows that ‘a multiplicity of logics still govern students’ choices and trajectories' (Sarauw & Madsen, 2020, p. 19) when it comes to the understanding of HE's purpose, and that the field has potentially widened and became more ambivalent instead of just replacing bildung (Tomlinson, 2017). This is also reflected in studies on the students' perceptions of quality (Jungblut et al, 2015).…”
Section: The Changing Understanding Of Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Students are able to resist, change and play with expectations towards them (Brooks, 2022; Tomlinson, 2017). This shows that ‘a multiplicity of logics still govern students’ choices and trajectories' (Sarauw & Madsen, 2020, p. 19) when it comes to the understanding of HE's purpose, and that the field has potentially widened and became more ambivalent instead of just replacing bildung (Tomlinson, 2017). This is also reflected in studies on the students' perceptions of quality (Jungblut et al, 2015).…”
Section: The Changing Understanding Of Higher Educationmentioning
confidence: 99%
“…Furthermore, it is crucial to centre the student's understandings because they can reveal if official policies and societal or political expectations of HE are reproduced, altered or resisted by students (Brooks, 2022). Previous studies have suggested that the relationship between the former and the latter is not straightforward (Nielsen, 2011;Sarauw & Madsen, 2020;Saunders, 2015). Most are national case studies or comparative studies across national higher education systems (HESs).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the taxonomy represents a conflation of well-being and learning that may contribute to pathologizing widespread student experiences. Based on the case study, we show how the well-being agenda marks a paradigmatic turn in higher education: Whereas the current student-centred paradigm has an outer orientation towards students’ performance in relation to predefined learning outcomes (Petersen and Sarauw, 2023; Sarauw and Madsen, 2020), the well-being agenda revolves around students’ inner psychological lives, which then become the subject and the object of education. This directs the educational attention towards the cultivation of particular kinds of subjects, mindsets and attitudes rather than educational relations, knowledge forms, and academic cultures and contexts.…”
Section: Introductionmentioning
confidence: 99%
“…While this comment was roundly criticised by many of those working in education for its overly narrow perspective, it is broadly representative of the assumptions that appear to underpin many HE reforms introduced across Europe over the past decade. These have included: obliging students to move more quickly through their studies so that they are able to enter the labour market sooner; encouraging employers to have a more direct input into curricula and sit on the governing boards of universities; highlighting the likely financial returns of specific degree programmes, to inform student decision-making; incentivising students to take up places on science, technology, engineering and maths (STEM) courses, on the basis of ostensible employer demand; and reducing the number of places available in subject areas that are deemed not to serve well the labour market (see, for example, Degn and Sørensen 2015 ; OfS 2020 ; Sarauw and Madsen 2020 ; Walsh and Loxley 2015 ). Moreover, students have also often been positioned discursively as first-and-foremost ‘future workers’ within many European HE policy documents (Brooks 2018b , 2021 ).…”
Section: Introductionmentioning
confidence: 99%